«Smart city» concept: genesis, priority development directions, problem aspects and ratings - Goloventchik, Galina G. (Journal of the Belarusian State University. Economics, 2020)
The article analyzes the phenomenon of smart city as the provision of modern quality of life through the use of innovative technologies that provide for economical and environmentally friendly use of urban life support systems. The author explores the theoretical foundations of the smart city concept, its multi-factor model, analyzes the stages of the evolution of smart cities, and provides examples of successful implementation of the concept in Amsterdam, Barcelona, Dubai, Copenhagen, San Francisco, and Stockholm. Special attention is paid to such technological innovations as the Internet of things, artificial intelligence, unmanned vehicles, robotics, blockchain technology, etc. The article analyzes the consequences of the implementation of the above-mentioned technologies, and considers the problems that arise in the functioning of smart cities. The concept of the proposed smart city commercial project for Minsk is briefly highlighted.